SOCIAL-PHILOSOPHICAL DESCRIPTION OF THE PHENOMENON OF YOUTH PATRIOTISM IN THE PROCESS OF SPIRITUAL GROWTH OF NEW UZBEKISTAN (Scientific journal of the Fergana State University, 2024)
In the article, the theoretical and methodological foundations of the socio-philosophical research of the phenomenon of youth patriotism in the process of spiritual growth of New Uzbekistan, the priority tasks of education of patriotism in young people in the process of spiritual growth of New Uzbekistan are studied. Also, the need to study the processes of spiritual growth of New Uzbekistan and the factors that develop it is analyzed.